2010
DOI: 10.1007/s00405-010-1471-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activities of histone H3, cyclin D1 and claudin 7 encoding genes in laryngeal cancer

Abstract: Uncontrolled proliferation and a decrease in cell-cell adhesion are one of the most important characteristics of malignancy. Determination of replication-dependent histone H3 can be applied as a proliferative marker. Cyclin D1 (CCND1) regulates the cell cycle by participating in the control of the G1/S phase transition. Claudins (CLDN) are components of tight junctions and may play an essential role in the loss of tissue cohesion. The aim of the study was to assess the mRNA expression of histone H3, cyclin D1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Cyclin D1 intense expression is seen in 40-70 % of LSCC. 10,11,20 In present study, cyclin D1 showed intense/significant expression in 31/72 (43%) patients.…”
Section: Cyclin D1supporting
confidence: 50%
See 1 more Smart Citation
“…Cyclin D1 intense expression is seen in 40-70 % of LSCC. 10,11,20 In present study, cyclin D1 showed intense/significant expression in 31/72 (43%) patients.…”
Section: Cyclin D1supporting
confidence: 50%
“…Numerous studies in the literature have stated the role of all these markers in tumorigenesis, diagnosis, prognosis as well as therapeutic management of the LSCC and other types of cancer. [8][9][10][11][12][13] The present study was postulated to study the expression of three proliferation markers in LSCC. The study also aimed to establish the correlation of all three proliferation markers with various clinical and histo-pathological parameters, treatment outcomes as well as survival in patients with LSCC.…”
mentioning
confidence: 99%
“…Modification on histone protein could affect the protein stability, protein-protein interaction, protein localization, and DNA binding [83]. Laryngeal carcinoma has a higher expression level of H3, however, the modification status of the overexpressed histone is not yet evaluated [84]. Takahashi et al reported that histone H3; was overexpressed in gastric adenocarcinoma and it was subjected to phosphorylation [85].…”
Section: Epigenetic Alterations In Human Malignanciesmentioning
confidence: 99%
“…A recent study showed that the inhibition of CCND1 suppresses cell proliferation in NSCLC cell lines ( Li et al, 2016 ). Several studies have reported the inhibition of cell proliferation, ( Chen et al, 2013 ; Zhu et al, 2010 ) suppression of cell cycle progression ( Chen et al, 2016 ; Kapral et al, 2011 ) and increased apoptosis ( Dai et al, 2016 ; Lai et al, 2010 ; Wang et al, 2014 ). In the present study, we also observed that GSK-J4 induced the suppression of CCND1 gene expression and might be responsible for the suppression of cell cycle progression, followed by the inhibition of cell proliferation and increased cell death.…”
Section: Discussionmentioning
confidence: 99%